2016
DOI: 10.1128/jvi.00521-16
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-155 Is Necessary for Efficient Gammaherpesvirus Reactivation from Latency, but Not for Establishment of Latency

Abstract: MicroRNA-155 (miR-155) has been shown to play significant roles in the immune response, including in the formation of germinal centers (GC) and the development and maturation of T follicular helper (Tfh) cells. There is in vitro evidence to support a critical role for cellular miR-155 and viral miR-155 homologs in the establishment of gammaherpesvirus latency in B cells. We sought to determine the contribution of miR-155 to the establishment and maintenance of latency in vivo using murine gammaherpesvirus (MHV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…LncRNAs are potentially implicated in determining glioma development through interaction with different signaling pathways or binding with miRNAs that have a wide range of targets . These in turn allow them to modulate many pathways that are critical to cancer progression, including proliferation, cell death, metastasis, angiogenesis and drug resistance pathways . We performed RNA pull‐down and nuclear–cytoplasmic subcellular location assays and demonstrated that HOXD‐AS1 was more likely to regulate molecular functions through ceRNA manner.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are potentially implicated in determining glioma development through interaction with different signaling pathways or binding with miRNAs that have a wide range of targets . These in turn allow them to modulate many pathways that are critical to cancer progression, including proliferation, cell death, metastasis, angiogenesis and drug resistance pathways . We performed RNA pull‐down and nuclear–cytoplasmic subcellular location assays and demonstrated that HOXD‐AS1 was more likely to regulate molecular functions through ceRNA manner.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of impaired Tfh cell generation, loss of miR-155 also leads to aberrant GC responses with reduced frequencies of GC B cells, lower amounts of antigen-specific antibodies, and defective secondary antibody responses [100][101][102][103]. Another interesting finding of this study was that the proliferation of antigen-specific cells in miR-155-deficient mice was impaired between days 3.5 and 4.5 after immunization, but not at earlier time points.…”
mentioning
confidence: 60%
“…As a consequence of impaired Tfh cell generation, loss of miR-155 also leads to aberrant GC responses with reduced frequencies of GC B cells, lower amounts of antigen-specific antibodies, and defective secondary antibody responses. [100][101][102][103] In addition to a Tfh cell-intrinsic role of miR-155, several studies confirmed that miR-155 is also highly expressed in GC B cells and controls the GC response upon immunization or viral infection by regulating the size and number of GCs, antibody production, class switch, and affinity maturation in a B cell-intrinsic manner. 94,[103][104][105] Since Tfh cells strongly depend on the interaction with GC B cells for their maintenance, miRNAs therefore also indirectly control Tfh cells through regulation of GC B cells.…”
Section: Themir-17~92clusterpromotestfhcell Differentiationandidentitymentioning
confidence: 96%
See 1 more Smart Citation
“…, and signaling coreceptors [67,82] Noncoding RNAs (including miRNAs) [41,42,48] Proteins interacting with oriLyts [51] Interferons and other cytokines [30,[32][33][34] Sensors of viral infection [23,83,84] Cell cycle proteins [62,85,86] Proteins regulating apoptosis [87][88][89][90] Transcription factors [91] DNA damage response proteins [5] Proteins involved in epigenetic gene regulation including chromatin assembly, histone modifications[ 3 _ T D $ D I F F ] , and DNA methylation [21][22][23][24][25][26][27][28]63,[92][93][94][95][96][97][98] Autophagy and xenophagy [99][100][101] Ubiquitination and NEDDylation [102][103][104][105] Chaperones [65] Post-translational modification proteins …”
Section: Key Figurementioning
confidence: 99%